2017
DOI: 10.1097/sla.0000000000001987
|View full text |Cite
|
Sign up to set email alerts
|

Acute Adverse Events and Postoperative Complications in a Randomized Trial of Preoperative Short-course Radiotherapy Versus Long-course Chemoradiotherapy for T3 Adenocarcinoma of the Rectum

Abstract: LC had significantly higher AEs compared with SC with no statistically significant differences in postoperative complications. There were clinical trends in permanent stoma rates and anastomotic leaks in favor of LC but with an increased perineal wound breakdown rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 16 publications
3
54
0
2
Order By: Relevance
“…Grade 3-4 RT induced toxicity must not be compared with surgical site infections or easily treated urinary tract infections. The Australian trial comparing SRT and CRT found no difference between the treatment groups regarding post-operative complications (53.2 % in SRT vs. 50.4% in CRT) 143 . In our material the post-operative complication rate was 50 % in SRT, 38 % in SRT-delay and 39 % in LRT-delay.…”
Section: Complications and Toxicitymentioning
confidence: 96%
See 1 more Smart Citation
“…Grade 3-4 RT induced toxicity must not be compared with surgical site infections or easily treated urinary tract infections. The Australian trial comparing SRT and CRT found no difference between the treatment groups regarding post-operative complications (53.2 % in SRT vs. 50.4% in CRT) 143 . In our material the post-operative complication rate was 50 % in SRT, 38 % in SRT-delay and 39 % in LRT-delay.…”
Section: Complications and Toxicitymentioning
confidence: 96%
“…Both the trials concluded that SRT with immediate surgery are not significantly different from CRT with respect of DFS, OS or rate of LR, but with more acute adverse events in the CRT group. [141][142][143] The optimal time interval within the first week is however debated. In a subgroup analysis from the Dutch TME-trial elderly patients (>75 years) were found to have worse survival if operated on 4-7 days after last RT, compared to having surgery performed 0-3 days after RT.…”
Section: Radiotherapymentioning
confidence: 99%
“…Owing to the amount of on going research comparing and evaluating neoadjuvant chemoradiotherapy protocols (e.g., short-course, delayed short-course, long course), recommendations continue to evolve, and certainly there remains equipoise in this area. 5,7,[33][34][35] This is reflected in the guidelines we examined, which differed in their endorsement of specific neoadjuvant protocols, as there is no definitive evidence yet for clinical practice.…”
Section: E33mentioning
confidence: 99%
“…Patients in the LCRT arm were more likely to have serious radiation dermatitis, and patients in the SCRT arm were more likely to have a permanent stoma. 10 , 11 The Stockholm III study showed noninferior oncologic outcomes with 2 SCRT regimens (immediate surgery and delayed interval to surgery) compared with LCRT. 12 Another trial comparing SCRT and LCRT, both with a delayed interval to surgery, showed greater tumor downstaging and downsizing with LCRT.…”
Section: Introductionmentioning
confidence: 99%